The economics of seed use and production for farmers and seed enterprises: The case of groundnut, millet and sorghum - Marenya, Paswel; Narmandakh, Davaatseren; Kirui, Leonard; Odhong, Jonathan A.; Templer, Noel A.; Agong, David; Opie, Hellen; Mchau, Devotha; Gerald, Alex; Martey, Edward; Sime, Mekonnen; Zemedu, Lemma; et al. (International Maize and Wheat Improvement Center, 2024)
This report examines the economic viability of seed businesses for dryland crops, with a special focus on sorghum, millet, and groundnut, in sub-Saharan Africa. It explores the profitability and growth potential of seed enterprises (including community-based ones), highlighting key challenges including limited access to quality seeds, low private-sector investment, and insufficient adoption of improved varieties by smallholder farmers. The analysis uses profitability metrics, including the ratio of seed cost to crop value and seed-to-grain increase ratios, to assess the financial sustainability of seed systems across multiple countries. Case studies from East and West Africa provide insights into the profitability of early-generation and certified seed production, demonstrating the importance of integrating private and public sector strategies to enhance economic seed production. The report offers policy recommendations aimed at strengthening seed systems through public-private partnerships, improving seed quality, and encouraging market development to support food security and sustainable agricultural growth in the region.